Owning Our Learning: Scaffolding Professional Inquiry for Educators (LEARNing Landscapes, 2011)
The authors advocate professional inquiry as purposeful, site-based learning for teacher leaders and school administrators. A key argument,social symmetry, proposes that creating engaged, inquiring learners requires teachers to own their learning through professional inquiry. A four-meeting model scaffolds collaborative inquiry from problem framing, through experimentation, and toward new convictions and commitments.The design of this professional inquiry platform has been informed by action research and school improvement and inspired by 21st Century Learning.
Keywords: inquiry; site-based learning; teacher leaders; administrator; social symmetry; professional inquiry; action research